Hand hygiene knowledge and practices among healthcare providers in a tertiary hospital, south west, Nigeria - Ekwere, Timothy Amos; Okafor, Ifeoma P (International Journal of Infection Control, 2013)
ABSTRACT Proper hand hygiene is an important means of preventing nosocomial infections. This study aimed to assess knowledge, attitude and hand hygiene practices among healthcare providers (HCPs) in Lagos University Teaching Hospital (LUTH), Lagos, South-West Nigeria. A cross-sectional study was conducted in August, 2011. Simple random sampling was used to select 500 HCPs (250 doctors and 250 nurses). Data collection was done with self-administered, structured questionnaires. Data obtained were analyzed with Epi-info 2008. A total of 430 HCPs (230 doctors and 200 nurses) participated in this study giving a response rate of 86%. Eighty-three percent had good knowledge; 97.6% had good attitude and 69.9% had good hand washing practices. Hand washing after contact with patient (97.7%) was better than before contact (61.4%). Nurses had better hand washing practices than doctors (Fisher’s exact p<0.001) and were more likely to wash their hands before patient contact than doctors (p<0.001). Training on infection control had a significant positive influence on HCPs knowledge and hand washing practices (Fisher’s exact p<0.001 and Fisher’s exact p<0.001) respectively. The commonly used hand-drying methods were common cloth towel (22.6%) and natural air drying (29.5%). The major motivation for hand washing was fear of contracting disease while the major constraint was busy work schedule in-between patient care. HCPs in LUTH have good hand washing knowledge but suboptimal practices especially with hand-drying. Hospital management should provide proper hand drying facilities, reduce work load and organize training on infection control on a regular basis. Key words: Infection control; hand washing; patient care; practice; healthcare providers; Nigeria